Soil-Structure Interaction in Transversely Isotropic Layered Media Subjected to Incident Plane SH Waves - Zhenning Ba; Xi Gao (Shock and Vibration)
The dynamic soil-structure interaction (SSI) for incident plane SH waves is analyzed for a two-dimensional (2D) model of a shear wall on a rigid foundation by using the indirect boundary element method (IBEM). The rigid foundation utilized in this study is embedded in transversely isotropic (TI) soil layers over bedrock. The accuracy of the IBEM method is verified and analyzed by setting a semicylindrical, rigid foundation-shear wall structure system in the single TI soil layer and multiple TI soil layers over bedrock. This study shows that the TI characteristics of the site have a significant impact on the effective input motion and the superstructure response. In a single soil layer, the increase in the shear modulus ratio in the vertical and horizontal directions has a certain degree of amplified action on the effective input motion and the superstructure response. Simultaneously, the corresponding peak frequency of the response increases. In multiple soil layers, the changes in the effective input motion and the superstructure response are also affected by the TI characteristics of the soil layers, and the impact of this effect is related to the sequence of the layers.